Individual Characteristics and Compliance with Personal Hygiene and PPE Use among Waste Pickers at Putri Cempo Landfill, Surakarta - Yulia Sari; Trivijaganita Lovinia; Yusuf Ari Mashuri; Sigit Setyawan (Gema Lingkungan Kesehatan, 2026)
Waste pickers face a high risk of disease due to continuous exposure to waste; however, adherence to personal hygiene and the use of personal protective equipment (PPE) remain suboptimal. This study aimed to analyze the relationship between individual characteristics and compliance with personal hygiene and PPE use among waste pickers at the Putri Cempo Landfill, Surakarta. An analytical observational study with a cross-sectional design was conducted among 46 waste pickers, selected through purposive sampling. The dependent variables were compliance with personal hygiene and PPE use, while the independent variables included age, gender, and education level. Data were collected using a structured questionnaire and analyzed using Fisher’s exact test. Most respondents demonstrated moderate compliance with personal hygiene and PPE practices. Statistical analysis indicated no significant association between gender (p = 0.182), age (p = 0.564), or education level (p = 0.602) and compliance behavior. Individual characteristics such as age, gender, and education were not significantly related to compliance with personal hygiene and PPE use. Therefore, interventions to improve compliance should prioritise organisational support and behavioral approaches, including education, training, and facility improvement, rather than focusing solely on demographic factors.